KONTEKS PRAGMATIK DALAM PERSPEKTIF CYBERPRAGMATICS - Kunjana Rahardi (Masyarakat Linguistik Indonesia, 2020)
It is always possible to combine the field of language with other fields which may be irrelevant, but there is a possibility to develop the fields synergistically. Cyberpragmatics can be seen as a transdisciplinary field, because it includes complex dimensions, namely language, pragmatics, technology, media, internet, and possibly other dimensions as well. This article aims to describe contexts in cyberpragmatics. The data was collected from utterances in various domains which contained context entities. The substantive data source was taken from authentic texts in various social media which also contained context. As for the locative data source, it was from social media that could be reached within the time of research. The data was collected by applying listening method and interview method. The researcher also used his intuitive judgment given the fact that he is a native speaker of Indonesian language. The data analysis method applied in this research is distributional analysis method in order to reach the linguistic aspects of this research. The dominant analytical method used is the extralingual type of extralinguistic method of analysis. The analysis showed that various pragmatic contexts were found, which include social context, societal context, cultural context, and situational context. The diverse contexts may change and shift over time. The context of the past cannot be the same as the context of the present and future. The elements and functions of the context will definitely shift and change so that the meaning of speech intentions in cyberpragmatics will also change.